Estado de infraestructura y gestión de residuos sólidos en los usuarios del mercado modelo, Iquitos, 2024 - Tello Huayamba, Estefanny Paola (2025)
The present quantitative study, with a non-experimental, descriptive, correlational and transversal design, analyzes the relationship between infrastructure improvement and efficiency in solid waste management in the Iquitos Model Market. We worked with a sample of 70 participants (50 merchants and 20 neighbors), selected through intentional sampling. For data collection, a survey with a structured 16-item questionnaire was used, whose reliability was verified with Cronbach's Alpha coefficient (0.779). The normality of the data was assessed using the Kolmogorov Smirnov test and the Spearman correlation coefficient was used for statistical analysis. The results indicate that the infrastructure improvement has optimized the frequency of waste collection; However, deficiencies persist in specific infrastructure and community participation, which shows the need for a comprehensive strategy. Despite daily collection in most areas, the lack of adequate containers and staff resources limits the effectiveness of the waste management system. The main deficiencies are related to the shortage of containers, equipment and effective separation and recycling programs, which generates dissatisfaction among merchants and users. The general perception reflects dissatisfaction with the lack of maintenance of the infrastructure, the presence of bad odors, vectors and the absence of separation programs. It is concluded that the market infrastructure indirectly influences waste management, its efficiency and sustainability being determinants to improve environmental conditions and user satisfaction.